Consumption and Distribution of Iodized Salt in Subamia Village Tabanan District 2014 - Manik Ulan Dewi; Kadek Tresna Adhi; Dyah Pradnyaparamita Duarsa (Public Health and Preventive Medicine Archive, 2016)
Background and purpose: Consumption of iodized salt is essential to prevent iodine deficiency disorders. One of the key success of iodized salt program is the distribution. This study explored the consumption and logistical distribution patterns of iodized salt among housewives in Subamia Village Tabanan District. Methods: The study was a qualitative with data collection using two focus group discussions (FGD) of 6 active and 6 inactive cadres. Indepth interviews were conducted with two health staffs, two community leaders, one staff of Trade/Industrial Office at Tabanan District and one salt seller. Data was analysed using thematic method. Results: Respondents preferred uniodized salt because of several reasons including less bitter, tastier and cheaper than iodized salt. Moreover, the distribution of iodized salt regulated by the government was reported to be impeded the salt distribution, this resulted in the difficulty of villagers to access the iodized salt Conclusion: Appetizing flavor, access and no local regulations on distribution of iodized salt is the cause of low consumption of iodized salt in Subamia Village Tabanan District.